The comparative Micro-CT analysis on trabecular bone density between hydroxyapatite gypsum puger scaffold application and bovine hydroxyapatite scaffold application - Amiyatun Naini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Generally, after tooth extraction, trauma is caused by bone damage, which leads to a decreased bone density. Bone damage repair should be conducted using a bone graft containing hydroxyapatite (HA). HA can be synthesised from gypsum puger powder, which is abundant and easy to obtain. Hydroxyapatite gypsum puger (HAGP) was successful with 100% hydroxyapatite purity level. Purpose: To compare the ratio of trabecular bone density in Wistar rats between HAGP scaffold application and bovine hydroxyapatite (BHA) scaffold application. Methods: This study is a laboratory experiment using 6 treatment groups, namely K (-) polyethylene glycol (PEG) 7, K (-) PEG 28, HAGP + PEG 7, HAGP + PEG 28, BHA + PEG 7, and BHA + PEG 28. HAGP scaffold freeze-drying. The rats were anaesthetised intramuscularly, and their left mandibular incisor was removed. The scaffold was applied to the mouse socket, followed by tissue decapitation after 7 and 28 days. The examination was carried out with micro-computed tomography (Micro-CT). Next, statistical analysis using a one-way analysis of variance (ANOVA) test was conducted (p <0.05). Results: The ANOVA test result showed a difference in bone density between the treatment and control groups on days 7 and 28. The Least Significant Difference (LSD) test result revealed that there was no significant difference between K (-) PEG 28 and HAGP + PEG 7 (p=0.133). Nevertheless, there were significant differences between the other groups. Conclusion: Based on the Micro-CT analysis, the trabecular bone density in Wistar rats following HAGP scaffold application is higher than that of BHA scaffold application.